Burmeister’s work on Scoliidae with especial reference to types and synonymy (Hymenoptera: Scoliidae). - Bradley, James Chester; Betrem, Johan George (Contributions to Entomology = Beiträge zur Entomologie, 1966)
The two authors have independently studied the Scoliidae of the Burmeister collection in the University of Halle. Professor Bradley was solely concerned with identifying holotypes and selecting lectotypes of Burmeister’s species. The results, along with the currently correct nomenclature of each nominal species, are recorded in the first part of this paper. Dr. Betrem has supplemented this with a study of the nominal Indo-Australian species of other authors recorded by Burmeister in his monograph. He has listed the correct identification and current name of each of these. Nomenclatural Acts leefmansi Betrem, 1928 (Campsomeriella), syn. n. of Campsomeriella agilis Smith campestris (Burmeister, 1854) (Campsomeris (Aelocampsomeris)), Lectotype described as Scolia campestris limosa (Burmeister, 1854) (Campsomeris (Xanthocampsomeris)), Lectotype described as Scolia limosa melanosoma (Saussure, 1859) (Carinoscolia), comb. n. hitherto Scolia melanosoma erythrosoma (Burmeister, 1854) (Liacos), comb. n. hitherto Scolia erythrosoma Burmeister, 1854 capitata (Burmeister, 1854) (Microscolia), comb. n. hitherto Scolia capitata Burmeister, 1854 aulica Burmeister, 1854 (Scolia), Lectotype now a synonym of Scolia (Discolia) dubia Say fervida Burmeister, 1854 (Scolia), Lectotype fimbriata Burmeister, 1854 (Scolia), Lectotype now a synonym of Campsomeriella collaris aureicollis (Fabricius, 1775) fulvofimbriata Burmeister, 1854 (Scolia), Lectotype fulvopilosa Banks, 1912 (Scolia), syn. n. of Campsomeris (Xanthocampsomeris) limosá (Burmeister, 1854) guttata Burmeister, 1854 (Scolia), Lectotype melanaria Burmeister, 1854 (Scolia), Lectotype now a synonym of Scolia (Discolia) ruficornis Fabricius erythropyga Burmeister, 1854 (Scolia (Discolia)), Lectotype haematodes (Burmeister, 1854) (Scolia (Discolia) dubia), Lectotype described as Scolia haematodes